1998
DOI: 10.1523/jneurosci.18-16-06081.1998
|View full text |Cite
|
Sign up to set email alerts
|

The cAMP Transduction Cascade Mediates the Prostaglandin E2Enhancement of the Capsaicin-Elicited Current in Rat Sensory Neurons: Whole-Cell and Single-Channel Studies

Abstract: Treatment with proinflammatory prostaglandin E2 (PGE2) produced a transient sensitization of whole-cell currents elicited by the vanilloid capsaicin. The intracellular signaling pathways that mediate the initiation of this PGE2-induced sensitization of the capsaicin-elicited current in rat sensory neurons are not well established. Treatment with either forskolin (100 nM to 10 microM) or membrane-permeant analogs of cAMP, 8-bromo-cAMP (8-Br-cAMP) and chlorphenylthio-cAMP (10 microM to 1 mM), transiently sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
231
1
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(250 citation statements)
references
References 37 publications
(60 reference statements)
15
231
1
3
Order By: Relevance
“…Protein kinase C (PKC) is known to modulate activity of several ion channels. Potentiation of TRPV1 by PKC and agonists like bradykinin (BK) has been studied extensively (Lopshire and Nicol, 1998;Cesare et al, 1999a,b;Khasar et al, 1999;Premkumar and Ahern, 2000;Numazaki et al, 2002). Here, we demonstrate a functional downregulation of TRPM8 by activation of PKC resulting in inhibition of TRPM8-mediated channel activity and synaptic transmission in contrast to TRPV1, which is upregulated.…”
Section: Introductionmentioning
confidence: 50%
“…Protein kinase C (PKC) is known to modulate activity of several ion channels. Potentiation of TRPV1 by PKC and agonists like bradykinin (BK) has been studied extensively (Lopshire and Nicol, 1998;Cesare et al, 1999a,b;Khasar et al, 1999;Premkumar and Ahern, 2000;Numazaki et al, 2002). Here, we demonstrate a functional downregulation of TRPM8 by activation of PKC resulting in inhibition of TRPM8-mediated channel activity and synaptic transmission in contrast to TRPV1, which is upregulated.…”
Section: Introductionmentioning
confidence: 50%
“…The sensitization of VR1 by PKC requires the phosphorylation of VR1 at both Ser-502 and Ser-800 because mutations at both of these putative PKC sites blocks VR1 sensitization (31). Similarly, prostaglandin is also known to sensitize i cap in dorsal root ganglion neurons via the PKA pathway (38). The sensitization of VR1 by PKA requires phosphorylation of all three putative PKA consensus sites, namely, Thr-144, Thr-370, and Ser-502, because mutation of any of these three PKA sites blocks its sensitization to heat (39).…”
Section: Discussionmentioning
confidence: 99%
“…PKA is known to sensitize VR1, which augments I cap in response to repeated applications of capsaicin (38,39). VR1 has three putative phosphorylation motifs for PKA, namely, Thr-144, Thr-370, and Ser-502, of which Thr-370 and Ser-502 are common to CaMKII sites (1).…”
Section: Recovery Of I Cap After Desensitization By Camkii-mentioning
confidence: 99%
“…One way to overcome this would be to sensitize the receptor by phosphorylation. Previous studies have shown that the VR function could be modulated by phosphorylation or dephosphorylation (15,16,26). The findings by Tominaga et al (13) are of significance in that a similar sensitization of VRs could be achieved by stimulating metabotropic receptors that leads to phosphorylation of VRs.…”
Section: T He Capsaicin or Vanilloid Receptor (Vr)mentioning
confidence: 93%